The collection of digital traces in the investigation of online crimes - Apsimet, N.M.; Alimkulov, Ye.T.; Duisenbayeva, G.Zh. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The article is devoted to the study of methods of collecting digital traces in investigations of online crimes. The purpose of the study is to systematize existing approaches and evaluate their effectiveness.The scientific significance of the work lies in a comprehensive analysis of the legal, technical and ethical aspects of the use of digital traces. The article describes the stages of the data collection process, including the detection, identification, collection and preservation of information, as well as modern cyberforensis technologies. Special attention is paid to the use of artificial intelligence and machine learning methods to improve the accuracy and speed of data processing. The main results of the study demonstrate the importance of digital traces in establishing the facts of crimes. The work makes a significant contribution to the development of digital forensics, improving data analysis methods and law enforcement practice. The article emphasizes the importance of integrating digital traces into the criminal investigation process and their role in building an evidence base. The findings obtained have practical value for professionals in the field of digital forensics and can be used to develop new approaches to the investigation of cybercrimes and improve existing techniques.